2021
DOI: 10.1093/qjmed/hcab009
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation, COVID-19 and disease severity: a meta-analysis

Abstract: Objective: Current meta-analysis aims to understand the effect of oral supplementation of vitamin D on intensive care unit (ICU) requirement and mortality in hospitalized COVID-19 patients. Methods: Databases PubMed, preprint servers, and google scholar were searched from December 2019 to December 2020. Authors searched for the articles assessing role of vitamin D supplementation on COVID-19. Cochrane RevMan tool was used for quantitative assessment of the data, where heterogeneity was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 17 publications
6
70
1
3
Order By: Relevance
“…Observational study including 10 articles and nearly 3 lakh patients done by Liu et al (Dec 2020) showed that low vitamin D levels were associated with more frequently with COVID positivity [ 10 ]. In a similar meta-analysis [ 28 ] which included two RCTS [ 13 , 16 ] similar to our study along with a retrospective case control study [ 29 ], it was concluded that vitamin D supplementation had reduction of ICU admission rates but insignificant effect on mortality [ 28 ]. The different result from this study as compared to ours could be attributable to the inclusion of retrospective study [ 29 ].…”
Section: Discussionsupporting
confidence: 56%
“…Observational study including 10 articles and nearly 3 lakh patients done by Liu et al (Dec 2020) showed that low vitamin D levels were associated with more frequently with COVID positivity [ 10 ]. In a similar meta-analysis [ 28 ] which included two RCTS [ 13 , 16 ] similar to our study along with a retrospective case control study [ 29 ], it was concluded that vitamin D supplementation had reduction of ICU admission rates but insignificant effect on mortality [ 28 ]. The different result from this study as compared to ours could be attributable to the inclusion of retrospective study [ 29 ].…”
Section: Discussionsupporting
confidence: 56%
“…A somewhat similar meta-analysis published earlier in 2021 found no significant benefit of vitamin D supplementation on mortality in COVID-19; however, the meta-analysis had included only three studies. Besides, the authors had presented only unadjusted risk estimates, thereby failing to consider potential confounding factors [48]. On the other hand, we have pooled data from 13 studies and have provided adjusted apart from unadjusted risk estimates, to make the results more robust and generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with severe COVID-19 disease have lower status of vitamin D, zinc and selenium than mild and moderate disease patients (14)(15)(16). Preliminary evidence from intervention studies suggests that supplementation with these micronutrients protects from severe COVID-19 disease (17,18).…”
Section: Introductionmentioning
confidence: 99%